The Effect of Production Planning and Quality Control on The Final Product - Dwi Joko Siswanto; Diana Aulia Nuroktavia; Ickhsanto Wahyudi; Tantri Yanuar Rahmat Syah (Syntax Corporation Indonesia, 2022)
The purpose of this study was to determine the quality of products in furniture manufacturing companies, in fact, there are always defective products in the production process in the field. In order to achieve a quality final result, continuous planning and control must be carried out using the Quality Control Circle method. The sample taken in this study is the monthly report data available at PT Hema Medhajaya for the 2017-2019 period with a total sample size of 36. The statistical method used is multiple linear regression with calculations through SPSS version 25. The results of this study show that Production Quality Planning has a coefficient value. β regression of -0.189 with a tcount of -23.988 and a significance level of 0.000 <0.05, it can be concluded that production quality planning has a negative and significant effect on the final product. And quality control has a positive and significant effect on the final product result marked with a significance level of 0.000 <0.05 and a regression coefficient value β2 of 2.493. the results of the simultaneous significance test (Test F) in this study. The results obtained are in the form of Fcount of 323,988 and a significance value of 0.000 <0.05. So it can be concluded that the variables of the Effect of Quality Planning and Quality Control together have a significant effect on the Final Production Result at the Furniture company at PT Hema Medhajaya.